The paradox of the alien plant Leucaena leucocephala subsp. glabrata (Rose) S. Zárate in Sicily: another threat for the native flora or a valuable resource? (International Journal of Plant Biology, 2020)
With this contribution, an updated picture of the rapid expansion of Leucaena leucocephala subsp. glabrata in Sicily is provided. On the one hand, this is a quite worrying sign, as this woody species figures among the world’s worst invasive alien species. On the other hand, the species shows interesting potential for production purposes (for wood, biomass and for feeding livestock), also considering its nitrogen fixation ability. Consequently, the two opposite options to cope with this species, i.e. cultivation and control/eradication, should accurately take into account the possible uses as well as its invasive behaviou